The Develoment of Speed Punch Reaction (SPR) as a Tool for Reaction Speed of Karate Punch Training (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
Developing reaction speed of punch training tool design for Karate which serves to improve the reaction speed of karate athletesâ€™ punch, so the training program will be more efficient in terms of time and power. The type of this study is R and D (Research and Development) research method. The study was conducted in two places, namely: Pusat dan Latihan Olahraga Pelajar (PPLOP) Jawa Tengah and Universitas Negeri Semarang 2017, for the testing of the tool, it was used by 16 athletes consisting of 8 junior karate athletes and 8 senior karate athletes. The final result of the reaction speed of punch traning tool on Karate â€œSpeed Punch Reactionâ€ that the tool can be used by junior or senior athletes to practice the reaction speed of punch. The tool validation results from karate expert scoring rubric and equipment expert got score 94 (exact) while the effectiveness of speed punch reaction model was obtained from karate expert evaluation on small and large scale of testing by 2 experiments and 16 athletes stated that Speed â€‹â€‹Punch Reaction tool is effective to be used to train the reaction speed of punch.